Hydrolysis of poly(l‐lactide)/ZnO nanocomposites with antimicrobial activity. Issue 28 (28th March 2019) - Pérez‐Álvarez, Leyre; Lizundia, Erlantz; Ruiz‐Rubio, Leire; Benito, Vanessa; Moreno, Isabel; Vilas‐Vilela, José Luis
ABSTRACT: This work investigates the effect of the incorporation of zinc oxide (ZnO) nanoparticles within a poly(l ‐lactic acid) (PLLA) matrix as an approach to speed up the hydrolysis of PLLA film surfaces. Hydrolysis was done by immersing nanocomposite films having 1 wt % of ZnO in 0.25 M sodium hydroxide at 58 °C. This concentration has been selected as it provides the maximum changes of physicochemical properties of hosting PLLA matrix. The evolution of the thermal properties, ultraviolet–visible transparency, wettability, and morphology were monitored at different time points. The amount of carboxylic groups onto PLLA/ZnO surfaces was quantified according to Toludine Blue‐O assay. Hydrolysis was mainly limited to film surfaces, which were grafted by carboxylic groups as a result of the random scission of PLLA ester linkages. The presence of such functional groups decreases the inherent surface hydrophobicity of PLLA at short hydrolysis times. On the contrary, long hydrolyses increase the hydrophobicity as a result of surface nanostructuring induced by the degradation of PLLA to water‐soluble oligomers. Overall, ZnO nanoparticles enable shorter surface modification times and provide a quick approach for the modification on the polarity of polylactide surfaces. The potential of hydrolyzed films as antimicrobial materials was explored using Gram‐negative Escherichia coli as a model. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47786. Abstract :